Analysis of the Mathematical Comprehension Ability of Grade XI Students on Story Problems Material on Arithmetic Sequences and Series - Violina Almaghfiroh; Taufiq Satria Mukti (Universitas Islam Sultan Agung, 2022)
The purpose of this study was to obtain a profile of the mathematicalunderstanding ability of class XI students on story problems in ArithmeticSequences and Series material. Qualitative research methods were used in thisstudy, with descriptive analysis techniques. The research was conducted at SMAN1 Rogojampi with 38 class XI students as the research subjects. The researchinstrument is a test to analyze comprehension skills and interview guidelines.Several stages of research are planning, implementation and observation. Then,explore students' mathematical understanding abilities by using 4 test items. Afterthat interviews were conducted with students. The results in this study stated thatthe level of students' mathematical understanding ability was classified as in themedium category. It could be seen that overall students were still lacking inunderstanding the concept of the material so they could not use the formulacorrectly when answering the questions given.